2023
DOI: 10.3389/fvets.2023.1110573
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the causative agents of Focal Ulcerative Dermatitis in commercial laying hens

Abstract: Focal Ulcerative Dermatitis (FUDS) is an emerging dermatological disease that affects cage-free laying flocks, it is characterized by the development of a lesion on the dorsum of the birds; FUDS is sporadic in nature and can result in a drop in egg production and up to 50% of cumulative mortality. A total of two cage-free flocks (flock 1: no history of FUDS; flock 2: birds affected with FUDS) from a commercial laying hen operation in the mid-west U.S. were sampled in this study. The microbial composition of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Moreover, M. lentus and M. sciuri are considered etiological agents of exudative epidermitis with zoonotic potentials [ 70 ]. Much more recently, whole-genome data of non- aureus staphylococci species have led to the identification and characterization of numerous putative virulence factors [ 71 , 72 , 73 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, M. lentus and M. sciuri are considered etiological agents of exudative epidermitis with zoonotic potentials [ 70 ]. Much more recently, whole-genome data of non- aureus staphylococci species have led to the identification and characterization of numerous putative virulence factors [ 71 , 72 , 73 ].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Moreover, M. lentus and M. sciuri are considered etiological agents of exudative epidermitis with zoonotic potentials [70]. Much more recently, whole-genome data of non-aureus staphylococci species have led to the identification and characterization of numerous putative virulence factors [71][72][73]. The finding of a beta-lactam-resistant S. edaphicus strain from an antarctic environment sample showed that the mecC gene located between a pseudo-staphylococcus cassette chromosome mec (ψSCCmecP5085) and other SCCs implies the integration and exchange of foreign DNA [54].…”
Section: Ecology Of Mecc Gene In Non-aureus Staphylococci and Mammali...mentioning
confidence: 99%
“…However, it is estimated that bacteremia accounts for up to 62% mortality in broiler breeders [266], while mortality rates due to endocarditis outbreaks in flocks are between 29 and 36% [266][267][268]. Lastly, a dermatological disease called Focal Ulcerative Dermatitis Syndrome (FUDS) has recently been reported in cage-free laying flocks [269]. FUDS is characterized by the development of lesions on the dorsal regions of the birds, next to the sebaceous uropygial gland [269].…”
Section: Staphylococcal Infections In Chickenmentioning
confidence: 99%
“…Lastly, a dermatological disease called Focal Ulcerative Dermatitis Syndrome (FUDS) has recently been reported in cage-free laying flocks [269]. FUDS is characterized by the development of lesions on the dorsal regions of the birds, next to the sebaceous uropygial gland [269]. Hens with clinical signs of FUDS experience significant decreases in egg production and loss of life [269].…”
Section: Staphylococcal Infections In Chickenmentioning
confidence: 99%
See 1 more Smart Citation